Pemikiran Muthahhari tentang Manusia Masa Depan sebagai Subyek Dakwah - Sanusi, Irfan (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2012)
This paper departed from Muthahhariâs statement that human nature in Islam is paradoxical creatures. In itself there are good qualities and have a tendency to go towards the truths and sacred entities, and the nature of evil as well. All of this is the potential of the human being and should establish itself to become a more perfect self. In view Muthahhari, man as the vicegerent of Allah on earth and as the preaching subjects in which have the nature of God confess, free reliable. Humans as subjects of daâwah initiated the tendency towards good and evil, with their capacity that is not limited, having a whole and instinctive dignity, human driving motivation in many ways is not only material but is transcendent (divine) that finally can freely make use of the grace and gifts bestowed him that will shape the future humans as subjects propaganda bright, awakened, has theistic and spiritual freedom and not experiencing alienation of the self, the world and God.